The Role of Emotions in The Formation of Social Relationships in Primary School-Age Children: A Psychological and Educational Approach - Ertanti, Devi wahyu; Hanurawan, Fattah; Suciptaningsih, Oktaviani Adhi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
The present study aims to examine the influence of emotions on the formation of social interactions among primary school-aged children in Malang City. The research sample consisted of two hundred children selected randomly from ten public or private elementary schools. The frequency and intensity of children's emotional expressions and emotional management abilities were primarily assessed through questionnaires and observation guides. Diverse aspects of social interactions and emotions were evaluated using a Likert scale ranging from